MARKETING STRATEGY AND ITS EFFECT TO THE CONSUMER PURCHASE INTENTION TOWARDS “KURMELO” (CANDIED POMELO ORANGE PEEL) IN WIJAYA KUSUMA AGRO-INDUSTRY MAGETAN REGENCY, EAST-JAVA, INDONESIA - Aprilia Roudzotul M; Budi Setiawan (Socio-Economics/Agribusiness Department, 2017)
This study aims are to analyze the effect of marketing strategy – product, price, distribution, promotion – to the consumer purchase intention towards “Kurmelo” (candied pomelo orange peel) in Wijaya Kusuma Agro-Industry, to describe internal and external factors as well as formulating marketing strategy. Method that used to analyze the effect of marketing strategy to the purchase intention is linear multiple regression with total respondent of 65 respondents. In formulating marketing strategy, this study employs SWOT analysis. The results confirms that marketing strategy variable, which is price, product, promotion, and place, simultaneously able to explain purchase intention of consumers. All those variables affect significantly to the purchase intention. Moreover, the result of SWOT analysis suggests that several strategies, such as promotion, production strategy, and market expantion, are encouraging in order to develop more Wijaya Kusuma Agro-Industri.